MOTIVASI ORANG TUA MENYEKOLAHKAN ANAKNYA KE MADRASAH TSANAWIYAH MUHAMMAD BASIUNI IMRAN SAMBAS - Bataria Bataria; Nuraini Nuraini; Astaman Astaman (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
The purpose of this study is to describe and analyze: 1) What encourages parents to send their children to Madrasah Tsanawiyah Muhammad Basiuni Imran Sambas for the 2019-2020 school year; 2) What parents need is to send their children to Madrasah Tsanawiyah Muhammad Basiuni Imran Sambas for the 2019-2020 school year; 3) The goal of parents to send their children to Madrasah Tsanawiyah Basiuni Imran Sambas for the 2019-2020 school year. This study uses a qualitative approach and the type of descriptive research. Data collection techniques used are observation, interviews and documentation. The data analysis techniques used are: data reduction, data display, verification, while the technique for checking the validity of research data uses: trust, dependence, and certainty. The results of the study show that: 1) What encourages parents to send their children to school, namely; encouragement from within, a). The existence of desire and desire, b). There is encouragement and need, c). The existence of hopes and ideals and d). Have a conducive environment. Encouragement from outside; a). The existence of religious values, b). Teacher quality, c). Good school environment, d). Distance from school and e). school achievement; 2) what parents need to send their children to school: a). The existence of physiological needs, b). The need for a sense of security, c). The need for love and affection, d). There is a need for self-esteem and e). There is a need for self-actualization. 3) The goals of parents to send their children to school are: a) So that children have a good religious foundation, b) So that children have intellectual intelligence and c) Comfort in school.